Prinsip Penulisan Bahan Ajar Bahasa Mandarin yang Efektif untuk Jurusan Komunikasi Pemasaran Universitas Bina Nusantara - Kelly Rosalin; Agustian Agustian (Lingua Cultura, 2014)
Article discussed the writing principles that must be considered in compiling Chinese language teaching material specifically used for Marketing Communication students regarding the interest and target of Marketing Communication of Bina Nusantara University. The methodologies used are descriptive quantitative for distributing questionnaires and qualitative approach through observation and interview. Research found the appropriate and effective Chinese language teaching material would enhance the standard of Chinese language learning. At present, Chinese language teaching material used by Marketing Communication students has not been able to fulfill their requirements. In addition, the target learners of the teaching material are universal.